2022
DOI: 10.1186/s13690-022-00927-x
|View full text |Cite
|
Sign up to set email alerts
|

Holistic antenatal education class interventions: a systematic review of the prioritisation and involvement of Indigenous Peoples’ of Aotearoa New Zealand, Australia, Canada and the United States over a 10-year period 2008 to 2018

Abstract: Background Research into the effectiveness of antenatal education classes is crucial for Indigenous Peoples from Aotearoa New Zealand, Australia, Canada and the United States who experience poorer maternal and infant health outcomes compared to non-Indigenous populations. Our systematic review questions were intended to determine the extent of Indigenous Peoples prioritisation and involvement in antenatal education classes, and to understand the experience of Indigenous Peoples from these count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Antenatal services are predominantly attended by women with higher levels of education and from the middle-to-upper socioeconomic strata across various developed nations, namely Canada and the United States [62,63], South Korea [64], and Belgium [65]. Regardless of immigration background, women attaining higher levels of education typically exhibit greater health literacy and autonomy in navigating their pregnancy [66,67]. As such, our study confirms that maternal educational level is the universal and most predictive determinant of ANE utilization, encompassing both women from refugee backgrounds and native Australians.…”
Section: Social Determinantsmentioning
confidence: 99%
“…Antenatal services are predominantly attended by women with higher levels of education and from the middle-to-upper socioeconomic strata across various developed nations, namely Canada and the United States [62,63], South Korea [64], and Belgium [65]. Regardless of immigration background, women attaining higher levels of education typically exhibit greater health literacy and autonomy in navigating their pregnancy [66,67]. As such, our study confirms that maternal educational level is the universal and most predictive determinant of ANE utilization, encompassing both women from refugee backgrounds and native Australians.…”
Section: Social Determinantsmentioning
confidence: 99%
“…Health care personnel must consider cultural and language differences when providing holistic antenatal educational sessions 14. A recent systematic review conducted by Barrett et al found that the Indigenous Peoples of New Zealand, Australia, Canada, and the United States (U.S.) have poor engagement and low participation in antenatal education classes 14. They recommended targeted interventions that consider culture, language, and wider aspects of holistic health 14.…”
mentioning
confidence: 99%
“…14 They rec-ommended targeted interventions that consider culture, language, and wider aspects of holistic health. 14 Engagement in CBE classes can empower these women and enhance coping behavior during the birthing process.…”
mentioning
confidence: 99%
See 2 more Smart Citations